Prevalence and Factors Associated with Teenage Pregnancy at Paynesville, Monrovia, Liberia: Facility Based Cross Section Study - (:unkn) unknown (My University, 2024)
Introduction: In Liberia, teenage pregnancy is a serious public health issue that causes social and economic hardship. Adolescent birth rates are among the highest in sub-Saharan Africa, according to statistics. There are significant differences in the prevalence of teenage pregnancy between and within nations. Most teenage pregnancies occur in places with poorer incomes and lower levels of education. The purpose of this research is to determine the prevalence of teenage pregnancy in Liberia and to investigate the risk factors related to it, particularly in the Paynesville city community of Duport Road cow field block "B.". Methods: The research that was done using the Duport Road Clinic as a resource center provided the data for this study. Fifty girls between the ages of 15 and 19 who visited the hospital and lived in the community throughout the study period were recruited as participants. Total population sampling was used to interview all 50 of the females. A population-based cross-sectional survey is used in this quantitative study to gather data, and IBM 20.0 SPSS was used for analysis. Results: According to the report, 50.2% of adolescent girls between the ages of 15 and 19 had started having children at the time of the survey. Teenage pregnancy in the community was significantly correlated with age (OR = 6.9; 95% CI: 4.647, 10.366, p – value 0.001), teenagers living with their parents (OR = 1.057; p > 0.001), non-use of contraception (OR = 2.53; 95% CI: 1.739, 3.683), and teenage girls who were aware of contraceptive methods (OR = 2.86, 95% CI = 0.443, 18.463). Conclusion: In conclusion, a number of factors, including early sexual initiation, cohabitation, lack of education, and contraceptive non-use, contribute to the high rate of teenage pregnancy in Liberia. Interventions including encouraging the use of contraception, discouraging early sexual beginning, and setting up family planning clinics are advised in order to lessen its
Keywords: African Research